Negara dan Masyarakat Sipil dalam Perspektif Sejarah Politik Indonesia - P. ANTHONIUS SITEPU (Politeia: Jurnal Ilmu Politik, 2010)
This study focused to explain about relation between state and civil society. Especially discuss opposition between them in political perspective approach.  Actually state and civil society are two of vital importance political elements in perspective politics. Both of them, is concept that expand along with era growth. Concept of civil society emerged as respond from state role that too dominant in society and concept of state emerged as respond from society that each other battle. But now, concept of civil society and state has expanded. There are there models relationships by them. First, civil society relations stands up as shield for society and state behavior that tend to hegemonic, authoritarian and repressive. Second, if state not hegemonic, civil society will emerge as state partner in executing public interest. Third, if public life already accommodated by country, civil society can do its function in complementary where civil society emerges to equip society needs. So, in this perspective concept of civil society comprehended as the element of democratization acceleration. Keywords: Civil society, State behaviour, democratization.